Catalyzing SDG 4: A Strategic Management and Edupreneurship Initiatives - Hamdan, Hamdan; Sunaryo, Deni; Edwards, John (Pandawan, 2025)
This study examines the intersection of entrepreneurship, strategic management, and education in contributing to the achievement of SDG 4. The bibliometric analysis covers research published from 2016 to 2024, focusing on the global trends and key themes that have emerged in strategic management and education. The United States, United Kingdom, and India have been identified as the leading nations conducting significant research in these areas. Notable themes such as sustainability, digital innovation, and education governance have emerged as central topics in the literature, reflecting their critical role in shaping the future of education. This paper investigates how strategic management practices can foster educational equity, sustainability, and innovation, providing essential insights into how educational systems can be optimized through strategic entrepreneurial approaches. The analysis highlights the importance of integrating entrepreneurship into strategic management to address educational challenges globally, particularly in the context of SDG 4, which aims to ensure inclusive and equitable quality education for all. The study further delves into how strategic management and entrepreneurship can align with the evolving demands of global education systems, ensuring adaptability and resilience in the face of technological advancements and changing societal needs. By exploring research trends and advancements within the 2016–2024 period, this study offers a comprehensive overview of the dynamic relationship between strategic management, education, and entrepreneurship, providing a foundation for future research and practical applications that contribute to the achievement of SDG 4. The findings underscore the pivotal role of entrepreneurship in educational reform.